Facultative anaerobic bacteria: key players in syntrophic fatty acids degradation under microaerophilic conditions - Magalhães, Carla Isabel Pereira (2021)
Anaerobic digestion (AD) is a mature technology that contributes to the sustainable development through the production of energy and products, using microbes as key players. Oxygen, formerly thought as the nemesis of AD, has been shown to benefit the AD processes when provided in vestigial doses [1]. The beneficial effects of micro-aeration have been attributed to the increased activity of facultative anaerobic bacteria (FAB). Besides being involved in fermentation and acidogenesis, FAB have been referred to act as a protective shield against the damaging effects of oxidative stress to the strict anaerobic communities [2]. However, their role in the syntrophic degradation of fatty acids is not clear. In this work, the relationship between syntrophic bacteria (Syntrophomonas wolfei (Sw) and S. zehnderi (Sz)), methanogens (Methanospirillum hungatei (Mh) and Methanobacterium formicicum (Mf)) and FAB (Pseudomonas strains (Ps)) was investigated, during the degradation of short (C4, butyrate), medium (C8, octanoate) and long (C16, hexadecanoate). The syntrophic co-cultures were pre-grown and the Pseudomonas spp. were further added, along with each substrate, over a range of O2 concentrations (0-2 % v/v). A second transfer was performed, exposing each of the cultures to O2 concentrations between 0-2% (v/v). In the presence of O2 (even at the lower concentrations) the activity of the syntrophic cocultures sharply decreased or even disappeared. However, in the presence of Pseudomonas, methane production occurred, reaching the theoretically expected at days 3, 8 and 28 under 0%, 1% and 2% O2, respectively. These results were obtained for C8 degradation in the presence of Sw+Mh+Ps. The same tendency was observed for C4 and C16 degradation with both consortia. Additionally, in the 2nd transfer, the cultures previously exposed to O2, maintained their activity being able of completely convert substrates to methane, under anoxic and microaerophilic conditions. These results show the essential role of Pseudomonas in the protection of syntrophic coculture activity allowing fatty acids degradation under microaerophilic conditions. Therefore, in real AD systems, where vestigial O2 can be detected, the presence of FAB may result in more stable, resilient, and functional syntrophic communities.